Desarrollo de modelo de éxito en la gestión financiera de las medianas empresas del sector metalmecánico basado en las buenas prácticas de ingeniería en finanzas para ser aplicado a las pequeñas empresas como la planificación financiera mediante sistemas de simulación y gestión por procesos - Ortigas Rengifo, Liliana Cristina (2016)
This thesis is the development of a plan or model of success for the process of Financial Management to be applied to a small company in the metalworking sector based on the research conducted for SMEs in the metalworking sector of Metropolitan Lima . Therefore the hypothesis of this investigation is to demonstrate that business growth is due to the implementation of plans, policies and actions organized based on established procedures , particularly in manufacturing and engineering of the same sector that can grow in enterprise size and increase earned income based on a model of financial management to improve financial planning, business valuation , planning and analysis of financial condition , collection , payment and financial control.